The role of Religion during the Civil War in Russia (on the example of processes in the Omsk and Pavlodar Diocese) - A. V. Sushko (Омский научный вестник: Серия "Общество. История. Современность")
Based on the example of the Omsk and Pavlodar Diocese, the article analyzes the influence of religion on the events of the Russian Revolution and the Civil War in Russia is analyzed. The religious factor is understood as the processes of the influence of religion on the beginning, course and outcome of the Civil War, on the activities of the opposing forces, political institutions and public opinion. The main thesis of this article is that in the Russian Revolution and the Civil War in Russia, for the majority of the population, religion did not play a consolidating pacifying role, but, on the contrary, became a factor in the disintegration of society and the escalation of civil confrontation. To confirm the main thesis, the author considers three aspects of the influence of the religion on the escalation of the Civil War in Russia. The first is the ideological conflict between the forces of the revolution and religious confessions, which naturally led the Church to the anti-Bolshevik camp. The second is conflicts between representatives of the clergy, caused by ideologically different views religious and political topics and support of socialist revolution by part of the clergy. The third is the decline in the authority of the Russian Orthodox Church as a social cultural institution among a significant part of the Orthodox population and among the non-Orthodox, which opened the way for the spread of varied ideologies of nationalism and socialism.